Analysis of Servicescape, Service Quality, and Product Quality on Consumer Purchasing Decisions of Padang Beach Culinary MSMEs - Reyngga Yusvika Aviandita; Rini Suryani; Fakhri Rabialdy; Bella Nissa; Azkia Dwi Sadira (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Increasing competition among culinary MSMEs in tourist destinations requires business owners to understand the factors influencing consumers’ purchasing decisions. This study aims to analyze the effects of servicescape, service quality, and product quality on consumers’ purchasing decisions at culinary MSMEs in Padang Beach tourism area. A quantitative approach was employed using a survey method involving 86 respondents selected through accidental sampling. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics 26. The results indicate that service quality and product quality have a positive and significant effect on purchasing decisions, while servicescape has no significant partial effect. Simultaneously, servicescape, service quality, and product quality have a significant effect on purchasing decisions. The Adjusted R Square value of 0.779 indicates that the three independent variables explain 77.9% of the variation in purchasing decisions, while the remaining 22.1% is explained by other factors outside the research model. Product quality has the strongest relative influence, with a Standardized Coefficient Beta of 0.445.